Estimating cardiovascular disease-free life-years with the addition of semaglutide in people with type 2 diabetes using pooled data from SUSTAIN 6 and PIONEER 6. (25th November 2020) - Westerink, J; Sommer Matthiessen, K; Nuhoho, S; Fainberg, U; Lyng Wolden, M; Visseren, F; Sattar, N
Abstract: Introduction: Cardiovascular disease (CVD) is the leading cause of disability and death in people with type 2 diabetes (T2D). In a post hoc analysis of pooled data (POOLED cohort) from two phase 3, randomized CV outcomes trials, SUSTAIN 6 (NCT01720446) and PIONEER 6 (NCT02692716), the addition of the glucagon-like peptide-1 analogue semaglutide to standard of care (SoC) in people with T2D at high risk of CVD significantly reduced the risk of major adverse CVD events (3-point MACE: CV death, non-fatal stroke and non-fatal myocardial infarction). Purpose: To estimate the effect of adding semaglutide to SoC on CVD-free life-years and 10-year CVD risk in patients with T2D by predicting individual patient-level risk of CVD events in the POOLED cohort using the DIAL CVD risk model. Methods: The 3-point MACE hazard ratio from the POOLED cohort (N=6480; HR = 0.76 [95% confidence interval [CI]: 0.62–0.92]) was applied to the patient-level lifetime risk of CVD events derived from the DIAL model. CVD-free life-years and 10-year CVD risk were then calculated based on the age-specific risks of CVD events and non-vascular mortality, using standard actuarial methods. Both new and recurrent CVD events were considered. The DIAL model was validated by comparing the predicted and observed number of CVD events after 1 year. The DIAL model was previously developed using data from people with T2D in the Swedish National Diabetes Registry and validated across geographical regions. Results: The DIAL model was considered valid for use in the POOLED cohort because the predicted number of CVD events at 1 year was within 5% of the number observed. Adding semaglutide to SoC was associated with a mean reduction in 10-year CVD risk of 20.0% (95% CI: 6.4–32.6%) and a mean increase of 1.72 (95% CI: 0.52–2.96) CVD-free life-years. The number of mean CVD-free life-years gained ranged from 0.62–2.91 years between age groups (Table). For a 60-year-old male with baseline characteristics matched to the average male from the POOLED cohort, adding semaglutide to SoC reduced 10-year CVD risk by 20.8% and provided 2.53 additional CVD-free life-years. The number of CVD-free life-years decreased when baseline age was increased (Figure). Conclusions: The addition of semaglutide to SoC was associated with a gain in CVD-free life-years. This analysis helps contextualize the results of CV outcomes trials and may help to inform clinical decision-making. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Novo Nordisk A/S